(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Reperfusion injury leads to damage to the hemodynamic and functional parameters of the kidney. This study investigated the effects of oral administration of the aqueous extract of rosemary on improvement of changes induced by ischemia-reperfusion in rats. Materials and Methods. Fourty male Sprague-Dawley rats were divided into 4 groups. One group was the control, rates in another group underwent sham operation, and 2 groups were exposed to reperfusion injury. Rats in one of the reperfusion groups was treated with 8% oral aqueous extract of rosemary (10 mL/kg/d) for 1 week (rosemary group), and the other received normal saline for the same period of time (reperfusion group). Reperfusion injury was induced by bilateral occlusion of the renal artery and vein for 30 minutes and reperfusion for 24 hours. Examination of oxidative stress was done, including measurement of malondialdehyde and ferric reducing antioxidant power in urine and blood samples. Histological studies were performed on excised kidneys. Results. The comparison between the rosemary and reperfusion groups indicated significant reductions in the levels of plasma creatinine, blood urea nitrogen, and absolute urinary excretion of sodium in the rosemary group. Similarly, the rosemary group presented a significant decrease in malondialdehyde and a significant increase in ferric-reducing antioxidant power. Histopathological examinations showed significant reductions in vascular congestion and cells exfoliation in the rosemary group, in comparison with the reperfusion group. Conclusions. Oral administration of the aqueous extract of rosemary prior to ischemia-reperfusion is effective in reducing functional and histopathological complications associated with acute kidney failure.